Human C-reactive protein aggravates osteoarthritis development in mice on a high-fat diet. Issue 1 (January 2019) - Kozijn, A.E.; Tartjiono, M.T.; Ravipati, S.; van der Ham, F.; Barrett, D.A.; Mastbergen, S.C.; Korthagen, N.M.; Lafeber, F.P.J.G.; Zuurmond, A.M.; Bobeldijk, I.; Weinans, H.; Stoop, R.
Summary: Objective: C-reactive protein (CRP) levels can be elevated in osteoarthritis (OA) patients. In addition to indicating systemic inflammation, it is suggested that CRP itself can play a role in OA development. Obesity and metabolic syndrome are important risk factors for OA and also induce elevated CRP levels. Here we evaluated in a human CRP (hCRP)-transgenic mouse model whether CRP itself contributes to the development of 'metabolic' OA. Design: Metabolic OA was induced by feeding 12-week-old hCRP-transgenic males (hCRP-tg, n = 30) and wild-type littermates ( n = 15) a 45 kcal% high-fat diet (HFD) for 38 weeks. Cartilage degradation, osteophytes and synovitis were graded on Safranin O-stained histological knee joint sections. Inflammatory status was assessed by plasma lipid profiling, flow cytometric analyses of blood immune cell populations and immunohistochemical staining of synovial macrophage subsets. Results: Male hCRP-tg mice showed aggravated OA severity and increased osteophytosis compared with their wild-type littermates. Both classical and non-classical monocytes showed increased expression of CCR2 and CD86 in hCRP-tg males. HFD-induced effects were evident for nearly all lipids measured and indicated a similar low-grade systemic inflammation for both genotypes. Synovitis scores and synovial macrophage subsets were similar in the two groups. Conclusions: Human CRP expression in a background of HFD-induced metabolic dysfunction resulted in the aggravation of OA through increased cartilage degeneration and osteophytosis. Increased recruitment of classical and non-classical monocytes might be a mechanism of action through which CRP is involved in aggravating this process. These findings suggest interventions selectively directed against CRP activity could ameliorate metabolic OA development.